Certified Programs and Proofs First International Conference, CPP 2011, Kenting, Taiwan, December 7-9, 2011. Proceedings - Jouannaud, Jean-Pierre; Shao, Zhong (Springer eBooks., 2011)
This book constitutes the referred proceedings of the First International Conference on Certified Programs and Proofs, CPP 2011, held in Kenting, Taiwan, in December 2011. The 24 revised regular papers presented together with 4 invited talks were carefully reviewed and selected from 49 submissions. They are organized in topical sections on logic and types, certificates, formalization, proof assistants, teaching, programming languages, hardware certification, miscellaneous, and proof perls.